Enhanced detection sensitivity of Leptospira DNA using a post-deposition annealed carbon quantum dots integrated tapered optical fiber biosensor - Zainuddin, Nurul Hida; Chee, Hui Yee; Abdul Rashid, Suraya; Ahmad, Muhammad Zamharir; Zan, Zuraidah; Abu Bakar, Muhammad Hafiz; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir; Yaacob, Mohd Hanif (Elsevier, 2023)
Leptospirosis is an illness caused by a Leptospira bacterial infection, and it can be fatal if not correctly diagnosed and treated. This work explores the development of an optical biosensor that utilizes tapered optical fiber integrated with post-deposition annealed carbon quantum dots (CQDs) to improve Leptospira deoxyribonucleic acid (DNA) detection. A standard optical single-mode fiber was tapered before being deposited with CQDs. The surface properties of CQDs on the tapered optical fiber were then tuned using a simple, one-step annealing process. Leptospira probe DNA was covalently bonded to the annealed CQDs surface using several commercially available linkers. The detection was achieved through probe DNA fragments that were hybridized into different concentrations of complementary target DNA. The biosensor limit of detection remained at 1.0 fM, but a better sensitivity of 2.321 ± 0.048 nm/nM was obtained. The affinity towards Leptospira complementary DNA improved as the equilibrium dissociation constant value was lowered to 0.15 Ñ… 10ˆ’ 9 M compared to previous studies. In non-complementary DNA reactions, a minimal wavelength shift is detected, indicating the biosensors high specificity, whereas studies using genomic DNAs from Leptospira and Clostridium difficile (as a control for genomic DNA) revealed similar observation. The integration of CQDs has achieved these remarkable biosensor traits, which hold great potential for developing a reliable leptospirosis diagnosis.